The Role of Local Government Financial Performance in Achieving Sustainable Development Goal 11 - Sari, Maya; Bakry, Mohammad Iqbal; Yuniar, Latifah Sukmawati; Furqan, Andi Chairil (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study examines the role of local government financial performance in achieving Sustainable Development Goal (SDG) 11, with a particular focus on Target 11.1 concerning access to adequate and affordable housing. The study is motivated by Indonesia’s persistent housing backlog and the extensive presence of slum settlements, alongside uneven fiscal capacity and suboptimal allocation of local budgets for the housing sector. The analysis employs panel data covering 542 local governments in Indonesia from 2019 to 2022, resulting in 2,144 observations, and applies a random effects panel regression model. The findings indicate that total solvency has a positive and significant effect on SDG 11 achievement, suggesting that stronger long-term fiscal capacity enhances sustainable urban development outcomes. In contrast, financial flexibility shows a significant negative effect, implying that excessive flexibility without clear development priorities may hinder SDG performance. Institutional age, population size, and archipelagic status as control variables also exhibit positive effects. Overall, the study underscores the importance of strengthening local fiscal governance to support sustainable housing development.